Development of hierarchical magnesium oxide anchored cerium oxide nanocomposites with improved magnetic properties and photocatalytic performance. (30th June 2020) - Rani, Neha; Chahal, Surjeet; Mahadevan, Santhosh Kumar; Kumar, Parmod; Shukla, Rajni; Singh, S K
Abstract: A facile strategy was introduced for the development of pure MgO and its nanocomposites using different CeO2 contents (3%–7%) to enhance their magnetic properties and photocatalytic performance. Different morphologies (namely nanoflowers and rhombohedral type nanostructures) were obtained using an in situ hydrothermal method at different concentrations of CeO2 . X-ray diffraction results revealed that peaks of CeO2 were observed along with peaks of MgO, which confirms the presence of both phases. The crystallite size and particle size were found to increase with changing CeO2 content in the host matrix of MgO. Moreover, the band gap reduces while the magnetic character increases with CeO2 content. The magnetic behaviour of the nanocomposites was elucidated on the basis of oxygen intrinsic defects, which are shown through XPS. EPR measurements were carried out to understand the valence electrons and establish the defects present in the material, which are related to the size of the nanostructures. The degradation of Rose Bengal dye was performed to probe the photocatalytic activity of the MgO@CeO2 nanocomposites. Hence the facile synthesis of these nanostructures conveyed good magnetic properties along with its application towards dye degradation.